1977
DOI: 10.1002/bjs.1800640718
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aneurysm in South African Negroes due to intimomedial mucoid degeneration

Abstract: Nine South African Negroes with abdominal aortic aneurysms due to intimomedial mucoid degeneration are described. These occurred in a younger age group than atherosclerotic aneurysms and with a female predominance. The aneurysms are not syphilitic in origin and are unlike atherosclerotic aneurysms. This form of abdominal aneurysm constitutes a distinct entity which is relatively prevalent in South African Negroes and which has hitherto received little or no emphasis and attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The mean age in the present study was 36.8 years, whereas the Decker series had a mean age of 51.1 years .' 1 Intimomedial mucoid degeneration is not unique to South African blacks. In 1973 Steiner et al described an abdominal aneurysm in a twenty-two-year old Ugandan woman.5 Histology revealed increased ground substance of the media with a moderate loss of elastic fibers in the aneurysmal wall.…”
Section: Discussionmentioning
confidence: 98%
“…The mean age in the present study was 36.8 years, whereas the Decker series had a mean age of 51.1 years .' 1 Intimomedial mucoid degeneration is not unique to South African blacks. In 1973 Steiner et al described an abdominal aneurysm in a twenty-two-year old Ugandan woman.5 Histology revealed increased ground substance of the media with a moderate loss of elastic fibers in the aneurysmal wall.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have shown that aneurysms in IMMD affect a younger population group than what is found in conventional non-specific degenerative aneurysms. 1 , 4 , 6 As in this case, patients with IMMD have a high prevalence of hypertension, which aggravates the elastic tissue breakdown, resulting in aneurysm formation. 1 , 4 , 6 , 9 , 11 …”
Section: Discussionmentioning
confidence: 83%
“… 2 , 11 A striking feature on histological examination is the absence of any inflammatory reaction. 1 The features are distinct from cystic medial necrosis, in which only the media is affected by the mucin accumulation. 1 , 4 Cystic medial necrosis is also typically confined to the aorta, whereas IMMD has been found to involve extraaortic vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations